Proteomics Analysis of Escherichia coli Treated with Nanosilver: An Approach to Analyze the Bactericidal Action - Khatoon, Nafeesa; Alam, Hammad; Sardar, Meryam (Current Proteomics, 2020)
Background: Silver nanoparticles pose high antibacterial properties against multi drugresistant and non-resistant bacteria. However, bacteria acquire resistance against chemically synthesized silver nanoparticles after repeated exposure. Therefore, there is an inevitable need to understand the mechanistic behavior of silver nanoparticles. Objective: In this study, we have performed a complete proteomic analysis of Escherichia coli after the treatment with silver nanoparticles to find out the mechanism of bactericidal action of silver nanoparticles (AgNPs). Methods: Silver nanoparticles were synthesized using Artemisia annua leaf extract and incubated with Escherichia coli to elucidate the antibacterial assay by determining MIC and the effect on the growth pattern. Further total genome proteins were isolated from control and silver nanoparticles treated bacteria, which were identified by LC MS and Label free quantification analysis technique. Results: Total identified proteins were 293, out of which 11 proteins were exclusively present in treated bacteria; these are the proteins mainly expressed in stress conditions. Fold change analysis shows that 65 proteins were upregulated where stress proteins are overexpressed while membrane proteins were downregulated. Conclusion: This study reveals that silver nanoparticles inhibit the expression of cellular proteins and cause cell death. Such a study may be helpful in designing drugs against resistant microbes.
Keywords: stress proteins